Improving person-centred care for older persons with serious multimorbidity in LMICs - Duncan Kwaitana; Dorothee van Breevoort; Modai Mnenula; Kennedy Nkhoma; Richard Harding; Maya J. Bates (AOSIS, 2024)
Background: Few interventions are documented to meet person-centred needs of older people with serious multimorbidity in low- and middle-income countries where access to palliative care is limited. Most of the care in these settings is delivered by primary care health workers. Aim: This study reports the development and acceptability testing of a communication skills training and mentorship intervention for primary health care workers in Malawi. Setting: This study was conducted at Mangochi District Hospital in the south-eastern region of Malawi. Methods: Twelve primary health care workers (four clinical officers and eight nurses) working in the primary care clinics received the intervention. The intervention was designed using modified nominal group technique, informed by stakeholder interviews and a theory of change workshop. Acceptability is reported from thematic analysis of a focus group discussion with primary health care workers who received the intervention using NVivo version 14. Results: Older persons with serious multi-morbidity and their caregivers identified a need for enhanced communication with their healthcare providers. This helped to inform the development of a communication training skills and mentorship intervention package based on the local best practice six-step Ask-Ask-Tell-Ask-Ask-Plan framework. Primary health care workers reported that the intervention supported person-centred communication and improved the quality of holistic assessments, although space, workload and availability of medication limited the implementation of person-centred communication. Conclusion: The Ask-Ask-Tell-Ask-Ask-Plan framework, supported person-centered communication and improved the quality of holistic assessment. Contribution: This intervention offers an affordable, local model for integrating person-centered palliative care in resource-limited primary healthcare settings.